The Roles Of Sulūk In Spiritual Empowerment Of Woman Practitioners In Institut Latihan Ilmu Tarekat (Ilit) Manarah - Nur Izzati Nadia binti Mohd Dzolkifli (Universiti Sains Islam Malaysia, 2024)
Matric: 3202664 (FKP)